3D structure determination of a protein in living cells using paramagnetic NMR spectroscopy. Issue 67 (29th July 2016) - Pan, Bin-Bin; Yang, Feng; Ye, Yansheng; Wu, Qiong; Li, Conggang; Huber, Thomas; Su, Xun-Cheng
Abstract : The integration of site-specific labeling of proteins with a stable lanthanide binding tag, paramagnetic NMR spectroscopy and the GPS-Rosetta program presents an effective and fast way of determining the three-dimensional structure of a protein in living cells. Abstract : Determining the three-dimensional structure of a protein in living cells remains particularly challenging. We demonstrated that the integration of site-specific tagging proteins and GPS-Rosetta calculations provides a fast and effective way of determining the structures of proteins in living cells, and in principle the interactions and dynamics of protein–ligand complexes.